Clinical indicators for severe prognosis of scrub typhus - Sriwongpan P; Krittigamas P; Kantipong P; Kunyanone N; Patumanond J; Namwongprom S (Dove Medical Press, 2013)
Pamornsri Sriwongpan,1,2 Pornsuda Krittigamas,3 Pacharee Kantipong,4 Naowarat Kunyanone,5 Jayanton Patumanond,1 Sirianong Namwongprom1,61Clinical Epidemiology Program, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand; 2Department of Social Medicine, Chiang Rai Prachanukroh Hospital, Chiang Rai, Thailand; 3Department of General Pediatrics, Nakornping Hospital, Chiang Mai, Thailand; 4Department of Internal Medicine, 5Department of Medical Technology, Chiang Rai Prachanukroh Hospital, Chiang Rai, Thailand; 6Department of Radiology, Faculty of Medicine, Chiang Mai University, Chiang Mai, ThailandBackground: The study explored clinical risk characteristics that may be used to forecast scrub typhus severity under routine clinical practices.Methods: Retrospective data were collected from patients registered at two university-affiliated tertiary care hospitals in the north of Thailand, from 2004 to 2010. Key information was retrieved from in-patient records, out patient cards, laboratory reports and registers. Patients were classified into three severity groups: nonsevere, severe (those with at least one organ involvement), and deceased. Prognostic characteristics for scrub typhus severity were analyzed by a multivariable ordinal continuation ratio regression.Results: A total of 526 patients were classified into nonsevere (n = 357), severe (n = 100), and deceased (n = 69). The significant multivariable prognostic characteristics for scrub typhus severity were increased body temperature (odds ratio [OR] = 0.58, 95% confidence interval [CI] = 0.45–0.74, P < 0.001), increased pulse rate (OR = 1.03, 95% CI = 1.01–1.05, P < 0.001), presence of crepitation (OR = 3.25, 95% CI = 1.52–6.96, P = 0.001), increased percentage of lymphocytes (OR = 0.97, 95% CI = 0.95–0.98, P = 0.001), increased aspartate aminotransferase (every 10 IU/L) (OR = 1.04, 95% CI = 1.02–1.06, P < 0.001), increased serum albumin (OR = 0.47, 95% CI = 0.27–0.80, P = 0.001), increased serum creatinine (OR = 1.83, 95% CI = 1.50–2.24, P < 0.001), and increased levels of positive urine albumin (OR = 1.43, 95% CI = 1.17–1.75, P < 0.001).Conclusion: Patients suspicious of scrub typhus with low body temperature, rapid pulse rate, presence of crepitation, low percentage of lymphocyte, low serum albumin, elevated aspartate aminotransferase, elevated serum creatinine, and positive urine albumin should be monitored closely for severity progression.Keywords: severe scrub typhus, risk factors, rickettsial infection, complications